Impact of increased production on TOC to the Waste Water Treatment Plant : Piteå 750 - Lundberg, Johan (Luleå tekniska universitet, Industriell miljö- och processteknik, 2017)
Today there are strict demands regarding emissions to water and air from the Swedish industries. This degree project, conducted at Smurfit Kappa Piteå, will focus on the emissions of organic material in waste water from the paper mill. The overall goal was through dynamic simulations predict the Total Organic Carbon (TOC) emissions from the paper mill at the time a foreseen increase of production is implemented. The recovery boiler is currently a bottleneck in the process and the production of sulphate pulp has today its maximum capacity. This means that production growth will occur exclusively by increasing the intake of recycled fiber. The work started with a comprehensive mapping of TOC, in which ingoing pulps in pulp towers, head boxes and effluent flows were mapped. This was done over a period of two weeks and thus covered a whole production cycle. A TOC method evaluation was conducted where the most suitable analysis method was determined. Mapped data were thereupon evaluated and significant variables were identified. It was determined that use of recycled fiber was the single most important variable to TOC load from paper machine 1 (PM1), but also starch addition to paper machine 2 (PM2) was found to be significant. The work then continued with the simulation phase, consisting of two main parts. The first part consisted of preparatory work where the model was developed to be able to accurately measure TOC load to the waste water treatment plant. This part also included work to identify necessary process changes as a result of an increased production. The second part consisted of the simulation. Three different scenarios were simulated for each paper machine plus two scenarios for the recycled fiber plant. The dynamic simulation model was successively calibrated with respect to TOC concentration and trends followed the ones expected by experience. In the production increase scenario simulated, TOC load distribution between PM1, PM2 and recycled fiber plant will more evenly distributed compared to current ...